Finnish ECEC teachers ́ and leaders’ conceptions of educational neuroscience - Khidr, Alaa (2022)
Somewhere between education and neuroscience lies the interdisciplinary field of educational neuroscience (EN). Since its emergence, a debate has been ongoing about its ability to transform educational practices by science. The brain is central to learning, therefore, EN has the potential to inform educational theories, practice, and policy. As important as the literature indicates, no studies were found that investigated Finnish educators’ perceptions of EN in developing teachers’ training. Aiming to cover this gap in research, this study aimed to examine Finnish early childhood education and care (ECEC) teachers' and leaders' conceptions of EN and delineate the various ways of conceptualizing it.